So for this, I will be doing the elimination method. Firstly, multiply both sides of the first equation by 2:
![6x-8y=52\\2x+8y=-36](https://img.qammunity.org/2019/formulas/mathematics/college/ejk7417ljtkvyhsmmw3h2gtx07yumcp98t.png)
Next, add the two equations together to get
. From here you can solve for x.
For this equation, just divide both sides by 8 and your first answer will be
![x=2](https://img.qammunity.org/2019/formulas/mathematics/college/j2ylgqzlqmqlm551uh73cj4i3ylurdli25.png)
Now that we have the value of x, substitute it into either equation to solve for y:
![3*2-4y=26\\6-4y=26\\-4y=20\\y=-5\\\\2*2+8y=-36\\4+8y=-36\\8y=-40\\y=-5](https://img.qammunity.org/2019/formulas/mathematics/college/67ldxnqfmw5i45cp3ls3jpltzbnhf73aa9.png)
In short, the solution is (2,-5), or A.